2014
DOI: 10.1111/hepr.12350
|View full text |Cite
|
Sign up to set email alerts
|

High prevalences of hepatitis B and C virus infections among adults living in Binh Thuan province, Vietnam

Abstract: In Binh Thuan, prevalences of HBV and HCV infections are high, HBV genotype B and HCV genotype 6a are predominant, and horizontal HBV transmission may still occur. Therefore, raising the coverage of a universal HBV vaccination program may be an effective liver cancer control in Vietnam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 20 publications
3
38
1
3
Order By: Relevance
“…15 Nevertheless, the HBV prevalence from our study was lower than that the previous report among the general population in Thanh Hoa province (18.8%), 14 Thai Binh province (19.0%), 17 and Binh Thuan province (15.3%). 13 The lower prevalence rate observed in our study might be explained by the following reasons. Our participants were in an urban area, and most of them were in the young age group with relatively high educational level, implying that they could easily access health information and had higher health literacy, and conveniently receive medical services.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…15 Nevertheless, the HBV prevalence from our study was lower than that the previous report among the general population in Thanh Hoa province (18.8%), 14 Thai Binh province (19.0%), 17 and Binh Thuan province (15.3%). 13 The lower prevalence rate observed in our study might be explained by the following reasons. Our participants were in an urban area, and most of them were in the young age group with relatively high educational level, implying that they could easily access health information and had higher health literacy, and conveniently receive medical services.…”
Section: Discussionmentioning
confidence: 59%
“…5,8 However, some studies reported that the prevalence of viral hepatitis infection among beauticians was similar to the general population, [12][13][14] and were not able to link being a beautician to an increased risk of acquiring viral hepatitis. [9][10][11] In Vietnam, several studies reported that the HBV prevalence in the general population based on positive hepatitis B surface antigen (HBsAg) ranges from 8.8% to 20.5%, [12][13][14][15][16] indicating a considerable problem for the health system. Meanwhile, the HCV prevalence based on positive antibody against HCV (anti-HCV) among the general population ranges from 0.35% to 2.2%.…”
Section: Prevalence Of Hepatitis B Virus and Hepatitis C Virus Infectmentioning
confidence: 99%
See 1 more Smart Citation
“…Mother-to-child (perinatal) transmission is the most common mode of infection, followed by horizontal transmission from family members and close contacts during early childhood [1]. An estimated 6-25% of Vietnamese are chronically infected with HBV [2][3][4][5]. Hepatitis C virus (HCV) infection prevalence is lower, estimated at 0.5-4% [2,3,6].…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 6-25% of Vietnamese are chronically infected with HBV [2][3][4][5]. Hepatitis C virus (HCV) infection prevalence is lower, estimated at 0.5-4% [2,3,6]. However, higher HBV and HCV infection prevalences are reported among people living with HIV (PLHIV) and at risk for HIV in Vietnam, ascribed to overlapping behavioral risks for HIV, HBV and HCV exposures [3,7,8].…”
Section: Introductionmentioning
confidence: 99%